Banning pre-event rumination in social anxiety: A preliminary randomized trial. (December 2018) - Modini, Matthew; Abbott, Maree J.
Abstract: Background and Objectives: Pre-event rumination has a clear role in maintaining social anxiety according to cognitive models. However, it is unclear what specific strategies can address pre-event rumination for individuals diagnosed with SAD. The current study aimed to determine the effectiveness of a brief intervention on multiple aspects of pre-event rumination, state anxiety and performance and threat appraisals. Additionally, the trajectory of pre-event rumination was investigated over four days. Methods: Participants with SAD were informed they would be required to complete a speech task in four days' time and were randomised to an intervention (n = 27) or a non-active control group (n = 25). The intervention group were instructed to "ban" pre-event rumination using a metacognitive therapy technique known as detached mindfulness. All participants completed daily measures of pre-evet rumination that assessed frequency, uncontrollability, engagement and distress associated with pre-event rumination. On the day of the speech task, participants also completed state and cognitive measures before delivering the speech task. Results: The intervention group reported reduced frequency, uncontrollability and distress associated with pre-event rumination, compared to the control group. There was no difference between groups for performance and threat appraisals as well as state anxiety. Rumination is a stable and robust process, with an increase in frequency and associated distress 24 hours before a feared social situation. Limitations: The lack of an active control group precludes comparisons to more traditional cognitive-behavioural therapy strategies for pre-event rumination. Conclusions: Pre-event rumination is a durable process but banning pre-event rumination using metacognitive therapy techniques shows promise for specifically addressing this maladaptive process. Highlights: Effect of banning pre-event rumination via a metacognitive technique is investigated. The intervention significantly reduced aspects of pre-event rumination in SAD. Other state-based variables, such as state anxiety, were unchanged. Applying metacognitive therapy techniques to rumination in social anxiety should be explored further.